An algorithm for determination of the fracture angle for the three-dimensional Puck matrix failure criterion for UD composites - Wiegand, J; Petrinic, N; Elliott, B (2008)
A 3D matrix failure algorithm based upon Puck's failure theory has been developed. The problem of calculating the orientation of a potential fracture plane, which is necessary to assess the onset of matrix failure, has been addressed. Consequently, a fracture angle search algorithm is proposed. The developed algorithm incorporates a numerical search of function extremes which minimises the required computational time for finding the accurate orientation of a potential fracture plane. For illustration, the algorithm together with the three-dimensional Puck failure model has been implemented in LS-DYNA explicit FE code. The fracture angle search algorithm is verified using a virtual uniaxial compression test. © 2008 Elsevier Ltd. All rights reserved.